Perancangan dan Implementasi SMS Gateway Pada Dianas Kependudukan dan Pencatatan Sipil - Melladia (Jurnal TEFSIN ( Jurnal Teknik Informatika dan Sistem Informasi), 2023)
Office of Population and Civil Registration Agam are a government agency based in Lubuk Basung, Agam. As government agencies that serve the community, we need to develope better communication. Short Message Service or SMS is used as a communication by many people. The advantage of SMS are low cost, fast, and to the point. SMS Gateway is an application that utilizes SMS facility, which is used for data transmission that quick and short that allows a mobile phone user to get the information from the application. SMS gateway is an application system to send and receive SMS. SMS Gateway application is expected to further improve the quality of services provided by civil servants to the public in the making of the deed or letter - a letter dealing Capil service via mobile phone. So that people who are away from the office will not difficult to finding information and they also can access information anytime and anywhere. Software that is required to make SMS Gateway is Xampp, PHP, and MySQL. Application that support SMS Gateway is Gammu.